Contrastive Analysis Hypothesis and Second Language Learning - Khansir, Ali Akbar; Pakdel, Farhad (Journal of ELT Research, 2019)
This article aims to provide an overview of some of the issues related to contrastive analysis hypothesis in second language learning. Contrastive hypothesis is one of the branches of applied linguistics which concerns with the study of two systems of languages between first language and target language. Contrastive hypothesis has fairly played an important role in language studies. Thus, in recent years, contrastive analysis has been used in language teaching contexts, syllabus design, and language classrooms by language teachers over the world. Many research works have been done by many language researchers in different aspects of contrastive hypothesis and also error analysis in the world. Language teachers always see contrastive analysis as a pedagogical imperative in target language and they use it as a functional approach in language classroom. However, contrastive hypothesis follows the errors of language learners in second language education.